ショウワ キチ ニ オケル ナンキョク MAP ケイカク - 福西, 浩; フクニシ, ヒロシ; 平澤, 威男; ヒラサワ, タケオ; 川口, 貞男; カワグチ, サダオ; Fukunishi, Hiroshi; HIRASAWA, Takeo; Kawaguchi, Sadao (1985)
P(論文) 1982年から1985年の間, 国際的に実施される中層大気観測計画(MAP)の一環として, 南極の昭和基地においても総合的な極域中層大気観測が実施される。中層大気の観測方法として, 地上, 飛行機, 衛星を用いてのリモートセンシングおよび飛行機, 気球, ロケットを用いての直接観測を行う。地上からのリモートセンシングによる主な観測装置は, レーザレーダー, VHFドップラーレーダー, 赤外分光, ドブソン法分光器などである。この論文では, これらプロジェクトの概要を示す。 Coordinated observations of the polar middle atmosphere are being carried out at Syowa Station in Antarctica as part of the Middle Atmosphere Program (MAP) for 1982-1985. The middle atmosphere is measured by a combination of remote sensing techniques from the ground, aircraft and spacecraft and in situ measurements by aircraft, balloon and sounding rocket. The main ground-based remote sensing facilities are laser radar, VHF doppler radar, infrared spectrometer and Dobson spectrophotometer. This paper gives an outline of this project. departmental bulletin paper